2021
DOI: 10.3390/jcm10235614
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant and Adjuvant Immunotherapy in Early-Stage Non-Small-Cell Lung Cancer, Past, Present, and Future

Abstract: Lung cancer is worldwide the most common malignancy. Standard of care treatments for early-stage non-small-cell lung cancer (NSCLC) include surgery and adjuvant chemotherapy. However, these patients continue to have poor prognosis due to systemic or local relapse. Immunotherapy has been considered as a novel approach to improve survival in patients with early-stage NSCLC. Since immune checkpoint inhibitors have transformed the treatment of advanced NSCLC, there is a growing interest in the role of immunotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
(56 reference statements)
0
21
0
1
Order By: Relevance
“…The main adjuvant immunotherapy studies (NCT02595944, NCT02273375 and NCT02504372) have completed their recruitment, but no data are available yet. A review has recently reported ongoing adjuvant and neoadjuvant clinical trials [120].…”
Section: Adjuvant Situationmentioning
confidence: 99%
“…The main adjuvant immunotherapy studies (NCT02595944, NCT02273375 and NCT02504372) have completed their recruitment, but no data are available yet. A review has recently reported ongoing adjuvant and neoadjuvant clinical trials [120].…”
Section: Adjuvant Situationmentioning
confidence: 99%
“…revealed that patients with undetectable MRD might not benefit from adjuvant treatment in subgroup analyses ( 63 ). Furthermore, the MERMAID-1 and MERMAID-2 studies were launched in 2020 to evaluate the clinical application value of ctDNA-based MRD in predicting the benefits of adjuvant immunotherapy in NSCLC patients ( 45 , 64 ). Finally, according to previous studies, blood-based TMb ( 65 ), tumor infiltrating lymphocytes ( 66 ) and specific gene mutations such as STK11, KEAP1 and TP53 ( 67 ) have been reported as biomarkers predictive of the benefits of ICI treatment.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Neoadjuvant immunotherapy is considered another promising approach to improve survival in patients with resectable NSCLC and offers several advantages, such as the downstaging of the tumor, eliminating micrometastases earlier and improving tolerability. Related advances have been detailed in several reviews ( 64 , 74 , 75 ). CheckMate-816 was the first phase III neoadjuvant immunotherapy clinical trial for resectable NSCLC without EGFR mutations or ALK rearrangements ( 76 ).…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…If Ipilimumab is combined with Nivolumab, symptoms present 24 weeks after start of treatment, and if it is combined with Pembrolizumab, symptoms begin after 30.5 weeks on average ( Table 3 and Figure 2 ). Moisturizers may be recommended as a possible preventative measure for rash and pruritus due to their ability to improve skin hydration and provide a cooling effect from water evaporation, reducing itch symptoms [ 18 , 19 , 20 ]. Patients with other dermatologic adverse effects may be prescribed antipruritic medications or other topical steroids [ 18 ].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%